2003
DOI: 10.1046/j.1365-2044.2003.03124.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mechanical cleaning and thermal disinfection on light intensity provided by fibrelight Macintosh laryngoscopes

Abstract: SummaryThe increased use of thermal decontamination procedures for fibrelight laryngoscope blades, to comply with international guidelines, will have considerable economical effects. We evaluated the effect of mechanical cleaning plus thermal disinfection at 90°C, with or without subsequent steam sterilisation at 134°C, on light intensity provided by fibrelight laryngoscopes. After mounting the blades in a special frame with a built-in light source, light intensity was measured using radiometer ⁄ photometer. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…1 That finding is purportedly consistent with the results of the current study showing a 50% to 60% reduction in light intensity after 80 steam sterilizations without washing. However, when exposed to machine washing and sterilization at 134-C, the light intensity of reusable fiberoptic laryngoscope blades decreases by 75% after 75 cycles of washing and sterilization.…”
supporting
confidence: 91%
“…1 That finding is purportedly consistent with the results of the current study showing a 50% to 60% reduction in light intensity after 80 steam sterilizations without washing. However, when exposed to machine washing and sterilization at 134-C, the light intensity of reusable fiberoptic laryngoscope blades decreases by 75% after 75 cycles of washing and sterilization.…”
supporting
confidence: 91%
“…The studies have shown that, in general, better illumination 152,165 and luminance 45 are supplied by distal bulbs, not fiberoptic blades. 23,28,165 Blade design may also affect light delivery to the target area, particularly if the light tip can be occluded by the tonguein some straight blades, the light tip's location on the blade's left edge may render it susceptible to partial occlusion by the tongue, pharyngeal, or paraepiglottic tissues as the blade displaces the tongue to the left (Fig. 165 Conversely, fiberoptic blades have the advantage of a cool (and secure) light source, with easier cleaning considerations.…”
Section: B Direct Laryngoscope Lighting Considerationsmentioning
confidence: 99%
“…23-5). 23 A suboptimal connection between the handle and fiberoptic blade may also compromise illumination by allowing light to escape between the bulb source in the handle and its entry into the fiberoptic bundle in the blade. Miller, in the original report of his blade, also illustrated the need to place the light source close to the tip of the blade (Fig.…”
Section: B Direct Laryngoscope Lighting Considerationsmentioning
confidence: 99%
“…However, repeated steam sterilisation leads to decrease in the light intensity of laryngoscopes. [2] There is a need for a HLD agent which is both cost effective and easily available. In a questionnaire-based survey conducted by us at a regional conference in 2015 regarding awareness of disinfection practices of laryngoscopes, it was found that out of 150 respondents, 12% used only tap water for cleaning while 88% used a chemical agent after rinsing with water.…”
Section: Introductionmentioning
confidence: 99%